Self-managed weight loss by smart body fat scales ameliorates obesity-related body composition during the COVID-19 pandemic: A follow-up study in Chinese population - Huang, Xinru; Li, Mingjie; Shi, Yefei; Yao, Hongyun; Lei, Zhijun; Kou, Wenxin; Li, Bo; Shi, Jiayun; Zhang, Weiwei; Jian, Weixia (Frontiers in Endocrinology, 2022)
Background: Since 2020, the coronavirus disease 2019 (COVID-19) pandemic might change weight-related behaviors in Chinese population. Objectives: To explore the demographic characteristics of body fat scale users and changes in obesity-related body composition by self-managed weight loss during COVID-19. Further, we analyzed the factors associated with successful weight loss in overweight and obese people. Methods: The study included 107,419 Chinese adults registered in a smart app connecting to a body fat scale in 2020 to describe the demographic characteristics of body fat scales use by Unpaired Student's t-test and Chi-Square test. Overweight and obese participants with body mass index (BMI) of more than 24 kg/m2 were screened to investigate the independent factors associated with effective weight loss and body composition changes using multivariate logistic regression analyses. Results: During the pandemic, the number of participants increased rapidly. Over half of the participants were women and with normal baseline body mass index (BMI). Multivariate logistic regressions showed that age, gender, measurement frequency classification, baseline BMI, visceral adipose index and skeletal muscle rate were associated with weight loss and fat loss in the overweight and obese population by BMI classification. High-frequency measurement was the most important factor for effective weight and fat loss. In the population with normal weight obesity, younger age was the most significant factor for effective fat loss. Conclusion: During the COVID-19 pandemic, participation in self-monitored weight loss increased rapidly, and women accounted for the majority. We speculated men paid less attention to the prevention and remission of obesity compared with women according to baseline characteristics of all participants, it was necessary to raise men’s awareness of body composition self-monitoring. In addition, promoting the usage of smart body fat scales could contribute to more effective weight and fat loss in the obese population by BMI classification, and compared with the elderly people, young subjects might be easier to successfully lose fat in the population with normal weight obesity. Digital self-management by smart body fat scales could become a promising approach for the obese population to keep fit.